PCR diagnosis of Fasciola hepatica in field-collected Lymnaea columella and Lymnaea viatrix snails - Cucher, Marcela Alejandra (2006)
Fil: Cucher, Marcela Alejandra. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Parasitología; Argentina.